2021
DOI: 10.47470/0016-9900-2021-100-3-268-273
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the functional state of the body of young athletes practicing sports games

Abstract: Introduction. Maintaining and strengthening young athletes’ health is very important since a growing body is more sensitive than an adult one. The overload on young athletes’ bodies’ functional systems is much higher compared to their peers who do not engage in intense physical activities and sports. This study aimed to assess the functional changes in the body of young athletes practicing sports games in the training process. Materials and methods. The functional state of the body of young athletes practicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Cebanu et al found that family sports games are very important for people with autism. He studied the cardiovascular system, central nervous system, respiratory system, and musculoskeletal system of children with autism, and performed functional status assessments to determine the degree of risk of adverse functional changes [ 6 ]. Corresponding author found that if every child with autism is provided with the same opportunity to play family sports games, even a very small patient may obtain the effect of significantly improving the ability of language communication [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cebanu et al found that family sports games are very important for people with autism. He studied the cardiovascular system, central nervous system, respiratory system, and musculoskeletal system of children with autism, and performed functional status assessments to determine the degree of risk of adverse functional changes [ 6 ]. Corresponding author found that if every child with autism is provided with the same opportunity to play family sports games, even a very small patient may obtain the effect of significantly improving the ability of language communication [ 7 ].…”
Section: Introductionmentioning
confidence: 99%